Rzadkie powikłania elektrowstrząsów w przebiegu schizofrenii lekoopornej - Wierzbiński, Piotr; Strombek-Milczarek, Marta; Szpilewska, Małgorzata; Wierzbińska, Agnieszka; Zdanowicz, Anna; Florkowski, Antoni (Current Problems of Psychiatry, 2013)
Serious adverse events during electroconvulsive therapy in patient with treatment-resistant schizophrenia The case of a male patient suffering from paranoid schizophrenia was presented in this study. He revealed such psychopathological symptoms as delusions of remote control, delusions of thoughts insertion and auditory halucinationations. Pharmacological treatment with conventional antipsychotics available in Poland like zuklopentixol, sulpiride, perphenazine, apotrifluoperazine in combination with valproate was ineffective. Atypical antypsychotic drugs: olanzapine, quetiapine, amisulpride, risperidone, clozapine and sertindole in combination with valproate was ineffective either. Electrocovulsive theraphy was applied to a patient. During the first electroshock serious adverse event occured - status epilepticus. Due to complications during the first electroshock the patient required treatment with antipsychotics. Combined therapy was used. Remission was achieved in four weeks during combined treatment with aripiprazole (15 mg/Day) and valproate (1300 mg/Day).